Brine Migration and Impact‐Induced Cryovolcanism on Europa. Issue 21 (5th November 2020) - Steinbrügge, G.; Voigt, J. R. C.; Wolfenbarger, N. S.; Hamilton, C. W.; Soderlund, K. M.; Young, D. A.; Blankenship, D. D.; Vance, S. D.; Schroeder, D. M.
Abstract: Despite evidence for plumes on Jupiter's moon Europa, no surface features have been definitively identified as the source of the plumes to date. Furthermore, it remains unknown whether the activity originates from near‐surface water reservoirs within the ice shell or if it is sourced from the underlying global ocean. Here we investigate brine pocket migration, studied previously in the context of sea ice on Earth, as a process for transporting brine along thermal gradients. We show that the fracture system located in the center of Europa's Manannán crater is consistent with the formation of a subsurface brine reservoir. After the initial impact, residual aqueous melt concentrated via brine pocket migration as the target material cooled. Freezing and overpressurization then resulted in a cryovolcanic eruption. The volume of the emptied reservoir and the critical composition at the end of migration provide further constraints on the average salinity of Europa's ice shell. Plain Language Summary: Jupiter's satellite Europa has a subsurface ocean covered by an icy shell. We show how small pockets of brine can migrate within the ice from colder areas to warmer areas. This can happen even at very low temperatures, below the point where pure water would freeze, because the water becomes saltier and saltier as it migrates. By looking at an impact crater on Europa, which was initially warm in the center and cooled inward from its colder surroundings, we can study how the water migrated toward the center and formed a central water reservoir. As the final water pocket at the center of the crater started to freeze, the increasing pressure lead to a cryovolcanic eruption that emplaced brine onto the surface to form a prominent "spider" feature before the ice collapsed into the cavity below. Using a digital terrain model of the crater and collapse feature, we estimate how much water erupted and how salty Europa's ice shell is. Key Points: We introduce brine pocket migration as a mechanism for melt mobilization and a driver for cryovolcanism on icy worlds We apply brine pocket migration to Europa's Manannán crater and its central "spider" (araneiform) fracture system and collapse structure We show that understanding the concepts of brine pocket migration can also constrain the salinity of Europa's ice shell and ocean